Learning disability, autism and the Criminal Procedure (Scotland) Act. Issue 5 (20th August 2020) - Williams, Fionnuala; Warwick, Mike; McKay, Colin; Macleod, Callum; Connolly, Moira
Abstract : Purpose: This paper aims to investigate the use of Part VI of the Criminal Procedure (Scotland) Act 1995 (CPSA) for people with Learning Disability (LD) and/or Autism. This is in the context of a recent review commissioned by the Scottish Government into whether the provisions in the Mental Health (Care and Treatment) (Scotland) Act 2003 (MHA) meet the needs of these groups which would also affect associated legislation such as CPSA. Design/methodology/approach: All CPSA orders active on the 3 January 2018 were identified and analysed for a number of variables including diagnoses, detention length, level of hospital security and medication use. Findings: Of the 580 people on CPSA orders, 69 (11.9%) had LD and 27 (4.7%) had possible/definite Autism. Most people with LD (56.5%) did not have a mental illness or personality disorder. Most (81.2%) had mild LD. There were two patients whose only diagnosis was Autism. Mean duration of detention was longer for those with LD than for those without. Most patients with LD alone were prescribed medication (61.5%) and, if in hospital, were managed in low secure units (59%). Originality/value: The results indicate that people with LD or Autism are differently affected by the application of the CPSA from other people with mental disorders, and that this is potentially discriminatory, if it is not objectively justified . It supports the stance from the recent review that to reduce the potential for discrimination, substantial changes to MHA and CPSA should be considered in the wider review of the MHA in Scotland.